Climate and acute/subacute paracoccidioidomycosis in a hyper-endemic area in Brazil - Barrozo, Ligia V.; Mendes, Rinaldo Poncio [UNESP]; Marques, Silvio Alencar [UNESP]; Benard, Gil; Siqueira Silva, Maria E.; Bagagli, Eduardo [UNESP] (Oxford University Press, 2009)
Methods Stepwise regression of annual data was applied to model incidence, calculated based on 91 cases, from lagged variables: antecedent precipitation, air temperature, soil water storage, absolute and relative air humidity, and Southern Oscillation Index (SOI).Results Multiple regression analyses resulted in a model, which explains 49% of the incidence variance, taking into account the absolute air humidity in the year of exposure, soil water storage and SOI of the previous 2 years.Conclusions The correlations may reflect enhanced fungal growth after increase in soil water storage in the longer term and greater spore release with increase in absolute air humidity in the short term.
Keywords: Paracoccidioidomycosis; climate; environment